2002
DOI: 10.1007/s11738-002-0023-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparative developmental pattern of enzymes of carbon metabolism and pentose phosphate pathway in mungbean and lentil nodules

Abstract: The activities of enzymes of pentose phosphate pathway (PPP) viz. glucose-6-phosphate dehydrogenase, 6-phosphogluconate dehydrogenase and carbon metabolism viz. phosphoenol pyruvate carboxylase, NADP-isocitrate dehydrogenase and NADP-malic enzyme were measured in the plant and bacteroid fractions of mungbean (ureide exporter) and lentil (amide exporter) nodules along with the developing roots for comparison. The enzymes of pentose phosphate pathway in legume cytosol had higher activities at a stage of maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…NADP-ME catalyzes the oxidative breakdown of malate to form CO 2 and pyruvate in the C4 pathway. Its non-C4 functions include the provision of carbon skeletons for ammonia assimilation [ 78 ] and reductant for wound-induced production of lignin and flavonoids [ 79 , 80 ]. CA genes are also prone to duplication, which may enhance their ability to form more complex structures, as discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…NADP-ME catalyzes the oxidative breakdown of malate to form CO 2 and pyruvate in the C4 pathway. Its non-C4 functions include the provision of carbon skeletons for ammonia assimilation [ 78 ] and reductant for wound-induced production of lignin and flavonoids [ 79 , 80 ]. CA genes are also prone to duplication, which may enhance their ability to form more complex structures, as discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…Effect of sodium chloride on total soluble sugars (TSS, mg glucose g (1 DW) and total amino acids (mg g (1 DW) in M. truncatula and L. japonicus inoculated with S. meliloti GR4 and M. loti R7A strains, respectively. 142 M. Lo´pez and C. Lluch this enzyme activity provides carbon skeletons for ammonia assimilation (Chopra et al 2002) through the GS/GOGAT pathway by the synthesis of alphaketoglutarate (Scheible et al 2000). Thus, the increase of ICDH activity by the salinity might compensate for the carbon limitation that occurs in nodules under salt stress, as it has been previously suggested under water stress (Ga´lvez et al 2005).…”
Section: Lo´pez and C Lluchmentioning
confidence: 82%
“…NADP-isocitrate dehydrogenase activity (ICDH; EC 1.1.1.42) is considered to be one of the main sources of NADPH and substrates for energy-yielding metabolism of bacteroids, in addition to carbon skeletons for ammonia assimilation (Chopra et al 2002). This implies that ICDH might be of crucial relevance for the C/N balance within nodules under stress conditions and NADPH requirements by the antioxidant ascorbate/glutathione pathway, activated in nodules under salt stress conditions (Matamoros et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The predominant GS/GOGAT enzymes are chloroplastic GS2 and Fd-GOGAT and cytosolic GS1 and NADH-GOGAT (Tobin and Yamaya, 2001). Chopra et al, (2002) reported that GS and GOGAT function as the main route for the assimilation of fixed nitrogen while GDH may function at higher NH 4 + concentration in young and senescing lentil nodules.…”
Section: Resultsmentioning
confidence: 99%